(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses an important role of social solidarity and cooperation in achieving gender equality. Social solitivity and cooperation will help gender equality of equality, change social norms and implement inclusive policies. The article describes the forms, methods and advantages of social solidarity and cooperation. The article also provides recommendations for the development of social solidarity and cooperation in providing gender equality.